Adsorption Characteristics of Chitosan-Modified Bamboo Biochar in Cd(II) Contaminated Water - Anxiang Huang; Wenlian Bai; Shoulu Yang; Zhongwei Wang; Nengying Wu; Yanxiong Zhang; Ning Ji; Dan Li (Journal of Chemistry)
The purpose of this study was to fabricate a low-cost and eco-friendly adsorbent using bamboo biochar (BB), a kind of charcoal composed of high Brunauer–Emmett–Teller surface area and variety of functional groups, and chitosan as substrates for remediation of Cd(II) in Cd(II) contaminated water and characterized the functional group characteristics, surface morphology, and Cd(II) adsorption effect using the Fourier transform infrared (FT-IR), scanning electron microscope (SEM), and energy-dispersive X-ray spectrometer (EDS). Results showed that chitosan-modified bamboo biochar (CBB) provided more active adsorption sites (such as –NH2, –COOH, –OH, and C=O) on the surface to enhance the Cd(II) removal efficiency in Cd(II) contaminated wastewater. Meanwhile, the optimal pH, contact time, and dose of CBB on the Cd(II) removal efficiency are 7, 120 min, and 600 mg, respectively. In addition, the adsorption isotherm results revealed that the possible adsorption mechanisms might include surface adsorption, electrostatic adsorption, and ion exchanges. Furthermore, the maximum adsorption capacity (Qm) values predicted from the Langmuir model were 37.74 and 93.46 mg/g for BB and CBB, respectively, also indicating a potential application of CBB in practical wastewater. Desorption and regeneration of CBB were attained simultaneously and the results showed that even after five cycles of adsorption-elution, the adsorption and desorption of CBB exhibited a slight decline and still reached at 71.70% and 65.92%. Results from this study would provide a reference to functionalized CBB for Cd(II) adsorption in contaminated water.